Application and Regulation of the International Education Standards (Journal of Leadership, Accountability and Ethics, 2023)
The new reality demands a change in the professional profile in order to meet the challenges and requirements of the accounting profession; education plays a very important role in the formation and dissemination of the International Education Standards (IES), since the quality of a profession cannot be maintained and improved if those who enter the profession are not prepared to meet the established standards. Therefore, this chapter analyzes IES 1 Admission Requirements for Professional Accounting Education Programs and IES 2 Initial Professional Development, in their scope, objective and requirements of the normative standards published by the International Federation of Accountants (IFAC) in the professional field and their impact on the design of curricula in Higher Education Institutions.
Keywords: leadership; accountability; ethics; International Education Standards; professional competence; admission profile; learning outcome